Effects of exogenous zinc (ZnSO4·7H2O) on photosynthetic characteristics and grain quality of hybrid rice - Shang, Gao (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.